FREQUENT PELVIC PATHOLOGIES IN PRIMARY INFERTILITY ON DIAGNOSTIC LAPAROSCOPY - Dr Anam Manan; Dr Hira Isfand; Dr Lubna Aslam; Dr Amna Mnnan; Dr Shazina Sattar; Dr Muhammad Haider Ali (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives: To determine the frequent Pelvic Pathologies in primary infertility on diagnostic laparoscopy.Materials and Methods:  This prospective study was conducted at the multiple centers incuding North West General Hospital and Research Centre, Peshawar, Pakistan and Madina Teaching Hospital Faisalabad, Pakistan in the duration from July, 2023 to December, 2023. Total of 102 patients were enrolled. All the patients underwent laparoscopy. A predesign questionere were used to collect data. For statistical analysis we used SPSS Version 25.Results: The mean age of the participants was 30.91 years with a standard deviation of 6.10. Upon laparoscopic examination, it was determined that endometriosis accounted for the highest proportion of primary infertility cases, affecting 44.1% of patients. Following endometriosis, tubal blockage with adhesions and tubal patency with adhesions were observed in 7.8% of patients each. Conversely, tubal blockage with ovarian cysts and tubal patency with ovarian cysts were the least prevalent conditions, each affecting 3.9% of patients. Stratification of pathologies based on age group and duration of infertility revealed insignificant P-values in both cases.Conclusion: It was concluded that endometriosis followed by Tubal blockage and Tubal patency are associated with primary infertility in women.